Kepribadian Menurut Sigmun Freud dan Ibnu Sina Serta Implikasinya terhadap Pendidikan Islam - Salminawati; Dedi Sahputra Napitupulu (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The purpose of this research is to examine the notion of personality and its educational consequences according to Islamic and Western philosophies, using Sigmund Freud and Ibn Sina as examples. By tracking several authoritative written sources, this study employs a qualitative method to literature analysis. Following that, data will be picked, studied, evaluated, and presented. The findings indicated that the fundamental distinction between Sigmund Freud's and Ibn Sina's personality conceptions is in their approach to the concept of individual happiness. According to Sigmund Freud, pleasure is achieved when biological requirements are balanced against psychological and social concerns. According to Sigmund Freud, religion acts as a barrier to human fulfillment. Meanwhile, Ibn Sina's thesis presupposes that an individual's pleasure is contingent upon the completeness of his knowledge and reasoning. Happiness is not limited to this world but also extends to the hereafter. To attain near-perfect knowledge and reason, a unique method is required, one that is highly spiritual in character.